A New Sequence Type of Neisseria meningitidis Serogroup C Associated With a 2016 Meningitis Outbreak in Mali. (31st October 2019) - Sanogo, Yibayiri Osee; Guindo, Ibréhima; Diarra, Seydou; Retchless, Adam C; Abdou, Mahamadou; Coulibaly, Souleymane; Maiga, Mahamadou Farka; Coumaré, Mama; Diarra, Bakary; Chen, Alexander; Chang, How-Yi; Vuong, Jeni T; et al.
Abstract: In 2016, Mali reported a bacterial meningitis outbreak consisting of 39 suspected cases between epidemiologic weeks 9 and 17 with 15% case fatality ratio in the health district of Ouéléssebougou, 80 kilometers from the capital Bamako. Cerebrospinal fluid specimens from 29 cases were tested by culture and real-time polymerase chain reaction; 22 (76%) were positive for bacterial meningitis pathogens, 16 (73%) of which were Neisseria meningitidis (Nm). Of the Nm-positive specimens, 14 (88%) were N meningitidis serogroup C (NmC), 1 was NmW, and 1 was nongroupable. Eight NmC isolates recovered by culture from the outbreak were characterized using whole genome sequencing. Genomics analysis revealed that all 8 isolates belonged to a new sequence type (ST) 12446 of clonal complex 10217 that formed a distinct clade genetically similar to ST-10217, a NmC strain that recently caused large epidemics of meningitis in Niger and Nigeria. The emergence of a new ST of NmC associated with an outbreak in the African meningitis belt further highlights the need for continued molecular surveillance in the region.